Рани дијагностички значај серума ГДФ-15, РБП4 и СОЦС3 код тешке пнеумоније са сепсом: Серум ГДФ-15, РБП4 и СОЦС3 код тешке пнеумоније са сепсом - Wang, Ziyi; Ke, Zhener (Journal of Medical Biochemistry, 2025)
Objective: To explore the early diagnostic value of the serum levels of growth differentiation factor 15 (GDF-15), retinol binding protein 4 (RBP4), and cytokine signal transduction inhibitory factor 3 (SOCS3) in patients with sepsis caused by severe pneumonia (SP). Methods: A total of 110 SP patients admitted to our hospital from December 2023 to February 2025. Based on whether they acquired sepsis, the patients were split into two groups: 52 patients with sepsis and 58 patients without. Additionally, 114 healthy persons of the same age group who passed the health examination test in our hospital during the same period were selected as the control group. The levels of serum GDF-15, RBP4 and SOCS3 were detected via ELISA. Correlation analysis was conducted via the Pearson method. The factors influencing secondary sepsis in SP patients were examined using univariate and multivariate analysis. Serum GDF-15, RBP4, and SOCS3 levels were analyzed for diagnostic effectiveness using a receiver operating characteristic (ROC) curve. The regional differences in the ROC curves of the serum samples were analyzed via the paired comparison method. Results: RBP4 levels were substantially lower (P<0.05) while serum GDF-15 and SOCS3 levels were significantly higher in the study group. Compared with those in nonseptic patients, Serum GDF-15 and SOCS3 levels were considerably higher in SP patients in the sepsis group, whereas the level of RBP4 was significantly lower (P<0.05). The sepsis group’s APACHE II score was substantially higher than the nonsepsis group’s (P<0.05). The APACHE II score showed a favorable correlation (P<0.05) with the levels of serum GDF-15 and SOCS3 in SP patients. The serum RBP4 level was negatively correlated with the APACHE II score (P<0.05). Elevated levels of serum GDF-15 and SOCS3 and increased APACHE II scores are risk factors for sepsis in SP patients, whereas elevated serum RBP4 levels are a protective factor for sepsis in SP patients (P<0.05). The area under the ROC curve (AUC) of the combined diagnosis of secondary sepsis in SP patients by serum GFF-15, RBP4 and SOCS3 levels was 0.946. The AUC of the combined diagnosis was superior to that of the individual diagnosis (Z=1.970, 3.898, 3.188; P<0.05). Conclusion: Serum GDF-15, RBP4, and SOCS3 levels in SP patients fluctuate in tandem with the severity of the patient’s illness and subsequent sepsis. The combined diagnosis of these three factors has certain value for secondary sepsis in SP patients.